Molecular Imaging in Multiple Myeloma—Novel PET Radiotracers Improve Patient Management and Guide Therapy - von Hinten, Johannes; Kircher, Malte; Dierks, Alexander; Pfob, Christian H.; Higuchi, Takahiro; Pomper, Martin G.; Rowe, Steven P.; Buck, Andreas K.; Samnick, Samuel; Werner, Rudolf A.; Lapa, Constantin (Frontiers in Nuclear Medicine, 2022)
Due to its proven value in imaging of multiple myeloma (MM), including staging, prognostication, and assessment of therapy response, 2-deoxy-2-[18F]fluoro-D-glucose (FDG) positron emission tomography (PET) is utilized extensively in the clinic. However, its accuracy is hampered by imperfect sensitivity (e.g., so-called FDG-negative MM) as well as specificity (e.g., inflammatory processes), with common pitfalls including fractures and degenerative changes. Novel approaches providing a read-out of increased protein or lipid membrane syntheses, such as [11C]methionine and [11C]choline or the C-X-C motif chemokine receptor 4-targeting radiotracer [68Ga]Pentixafor, have already been shown to be suitable adjuncts or alternatives to FDG. In the present focused review, those imaging agents along with their theranostic potential in the context of MM are highlighted.